A new genus of Entomobryinae (Collembola, Entomobryidae) from Brazilian Amazon with body scales and dental spines - Cipola, Nikolas Gioia; Morais, José Wellington De; Bellini, Bruno Cavalcante (Zootaxa, 2016)
A new monotypic genus of Entomobryinae from Brazilian Amazon is described and illustrated. Amazhomidia gen. nov. is similar to other genera of the subfamily, especially to Sinhomidia Zhang, in presence of apically pointed scales on body dorsally and spines on dens. It differs from all other genera of Entomobryinae by the combination of: bifurcate prelabral chaetae, cephalic groove with scale-like chaetae and two transverse rows macrochaetae present on anterior central region of the abdominal IV segment. Amazhomidia ducke sp. nov., the type species of the new genus is described. An identification key to the genera of Entomobryidae with scales and dental spines is also provided.